Development Of Interactive E-Book Of Based Learning Media Canva In Recount Text Material For Class VIII At SMP Negeri 1 Hiliduho In 2023/2024: English - Meiwan Tuti Zendrato; Trisman Harefa; Adieli Laoli; Hidayati Daeli (Prodi Tadris Bahasa Inggris, 2025)
This study aims to develop a canva-based interactive ebook on recount text material, determine the quality and feasibility of the product and to determine the students' response to the ebook developed. This research uses the R&D (Research and Development) method with the 4D model, namely Define, Design, Develop and Dessemination. The data collection techniques used are free observation and questionnaires to obtain feasibility results and responses from students using a Likert scale. The data collection instrument is a questionnaire given to media expert validators, material expert validators and practitioner expert validators as well as the results of trials on students. The developed media was tested on 30 VIII grade students at SMP Negeri 1 Hiliduho. The findings of this study state that the interactive ebook learning media on Recount Text material designed and developed through the Canva application obtained a validation data value by media experts of 90% declared very valid with the category “very feasible”, by material expert validators of 86% declared valid with the category “very feasible” and by practitioner expert validators of 93% declared very valid with the category “very feasible”. The results of student responses to the product trial of interactive ebook learning media were declared very good with a percentage of 84.9% with the category “very feasible”. Based on the results of the product feasibility assessment and effectiveness trial using pretest and posttest, it can be concluded that the canva-based interactive ebook learning media on recount text material is very feasible and good to use in learning English.